Sustained Reduction in Third-generation Cephalosporin Usage in Adult Inpatients Following Introduction of an Antimicrobial Stewardship Program in a Large, Urban Hospital in Malawi. (15th February 2020) - Lester, Rebecca; Haigh, Kate; Wood, Alasdair; MacPherson, Eleanor E; Maheswaran, Hendramoorthy; Bogue, Patrick; Hanger, Sofia; Kalizang'oma, Akuzike; Srirathan, Vinothan; Kulapani, David; Mallewa, Jane; Nyirenda, Mulinda; et al.
Abstract: Background: Third-generation cephalosporins (3GC) remain the first-choice empiric antibiotic for severe infection in many sub-Saharan African hospitals. In Malawi, the limited availability of alternatives means that strategies to prevent the spread of 3GC resistance are imperative; however, suitable approaches to antimicrobial stewardship (AMS) in low-income settings are not well studied. Methods: We introduced an AMS intervention to Queen Elizabeth Central Hospital in Blantyre. The intervention consisted of a prescribing application for smartphones and regular point-prevalence surveys with prescriber feedback. We evaluate the effects of the intervention on 3GC usage and on the cost of providing antibiotics. Using a thematic analysis of semi-structured interviews and participant observations, we additionally evaluate the acceptability of the stewardship program. Results: The proportion of antibiotic prescriptions for a 3GC reduced from 193/241 (80.1%) to 177/330 (53.6%; percentage decrease, 26.5%; 95% confidence interval, 18.7–34.1) with no change in the case-fatality rate. The cost analysis estimated an annual savings of US$15 000. Qualitative research revealed trust in the guideline and found that its accessibility through smartphones helpful to guide clinical decisions. Operational health-system barriers and hierarchal clinical relationships lead to continued reliance on 3GC. Conclusions: We report the successful introduction of an antimicrobial stewardship approach in Malawi. By focusing on pragmatic interventions and simple aims, we demonstrate the feasibility, acceptability, and cost savings of a stewardship program where resources are limited. In doing so, we provide a suitable starting point for expansions of AMS interventions in this and other low-income settings. Abstract : An antimicrobial stewardship program, consisting of a prescribing guideline and point-prevalence surveys with prescriber feedback, was introduced at Queen Elizabeth Central Hospital in Malawi. The program was effective in reducing third-generation cephalosporin usage and was potentially cost-saving for the hospital.